Does Party Competition Affect Political Activism? - Anselm Hager; Johannes Hermle; Lukas Hensel; Christopher Roth (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Does party competition affect political activism? This paper studies the decision of party supporters to join political campaigns. We present a framework that incorporates supporters' instrumental and expressive motives and illustrates that party competition can either increase or decrease party activism. To distinguish between these competing predictions, we implemented a field experiment with a European party during a national election. In a seemingly unrelated party survey, we randomly assigned 1,417 party supporters to true information that the canvassing activity of the main competitor party was exceptionally high. Using unobtrusive, real-time data on party supporters' canvassing behavior, we find that treated respondents are 30 percent less likely to go canvassing. To investigate the causal mechanism, we leverage additional survey evidence collected two months after the campaign. Consistent with affective accounts of political activism, we show that increased competition lowered party supporters' political self-efficacy, which plausibly led them to remain inactive.
Keywords: 330; party activism; electoral competition; field experiment; campaigns